Investigating effects of polybenzimidazole loading design in the catalyst layer on the performance of polybenzimidazole‐based high‐temperature proton exchange membrane fuel cell through experiments and simulations. (14th February 2013) - Su, Ay; Ferng, Yuh‐Ming; Tsai, X. Y.; Karakoc, Hikmet; Midilli, Adnan; Turan, Onder
SUMMARY This study uses both experiments and simulations to investigate the effects of polybenzimidazole (PBI) loading design in the catalyst layer (CL) on the performance of a high‐temperature proton exchange membrane fuel cell (HTPEMFC). The performance of a self‐made PBI‐based HTPEMFC with various PBI loading in the CL are experimentally measured. A two‐dimensional (2D) simulation model is also developed to numerically predict the characteristics of the cell. The CL with single‐layer PBI loadings of 5, 10, 20, and 30 wt%; two‐layer PBI loadings of 5–30 wt%, and three‐layer PBI loadings of 5–10–20 wt% are considered. According to the experimental measurements, the performance of the PEMFC with the two‐layer CL design is similar to that of the PEMFC with the single‐layer of 10 wt% PBI loading design, superior to that of the single‐layer 20 wt% PBI loading design, and inferior to that of the single‐layer 5 wt% loading design. The measured current density versus voltage curve for the PEMFC with the three‐layer loading design matches that of the single‐layer 5 wt% PBI loading. The present model also captures these characteristics. Both the experimentally measured and the model predicted results demonstrate that the multilayer PBI loading design in the CL can offer the advantages of both lower and higher PBI loading, with the lower loading near the gas diffusion layer and the higher loading located near the membrane. Copyright © 2013 John Wiley & Sons, Ltd.